Influence of Distance to Scene on Time to Thrombolysis in a Specialized Stroke Ambulance. Issue 8 (August 2016) - Koch, Peter M.; Kunz, Alexander; Ebinger, Martin; Geisler, Frederik; Rozanski, Michal; Waldschmidt, Carolin; Weber, Joachim E.; Wendt, Matthias; Winter, Benjamin; Zieschang, Katja; Bollweg, Kerstin; Kaczmarek, Sabina; et al.
Abstract : Background and Purpose—: Specialized computed tomography–equipped stroke ambulances shorten time to intravenous thrombolysis in acute ischemic stroke by starting treatment before hospital arrival. Because of longer travel-time-to-scene, time benefits of this concept are expected to diminish with longer distances from base station to scene. Methods—: We used data from the Prehospital Acute Neurological Treatment and Optimization of Medical Cares in Stroke (PHANTOM-S) trial comparing time intervals between patients for whom a specialized stroke ambulance (stroke emergency mobile) was deployed and patients with conventional emergency medical service. Expected times from base station to scene had been calculated beforehand using computer algorithms informed by emergency medical service routine data. Four different deployment zones with–75% probability–expected arrival within 4, 8, 12, and 16 minutes and total population coverage of ≈1.3 million inhabitants were categorized for stroke emergency mobile deployment. We analyzed times from alarm-to-arrival at scene, to start of intravenous thrombolysis and from onset-to-intravenous thrombolysis. Results—: Corresponding to the size of the respective catchment zone, the number of patients cared increased with distance (zone 1: n=30, zone 2: n=127, zone 3: n=156, and zone 4: n=217). Although time to stroke emergency mobile arrival increased with distance (mean: 8.0, 12.5, 15.4, and 18.4 minutes in zones 1–4), time from alarm-to-intravenous thrombolysis (mean: 41.8 versus 76.5; 50.2 versus 79.1; 54.5 versus 76.6; and 59.3 versus 78.0 minutes, respectively; all P <0.01) remained shorter in the stroke emergency mobile group across all zones. Conclusions—: In a metropolitan area such as Berlin, time benefits justify a specialized stroke ambulance service up to a mean travel time of 18 minutes from base station. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01382862.